Hybrid BFGS-ZMRI methods with global convergence properties - Abidin, Z.Z.; Aini, N.; Husin, S.F.; Rivaie, M; Mamat, M. (2018)
In this paper, we focus on the steepest descent and quasi-Newton method in solving unconstrained optimization problem. Therefore, we develop a new search direction for hybrid BFGS-ZMRI method with global convergence properties. Based on the numerical result, our method shows significant improvement in the number of iteration and CPU time.